Influence of own mother's milk on bronchopulmonary dysplasia and costs. Issue 3 (2nd November 2016) - Patel, Aloka L; Johnson, Tricia J; Robin, Beverley; Bigger, Harold R; Buchanan, Ashley; Christian, Elizabeth; Nandhan, Vikram; Shroff, Anita; Schoeny, Michael; Engstrom, Janet L; Meier, Paula P
Abstract : Background: Human milk from the infant's mother (own mother's milk; OMM) feedings reduces the risk of several morbidities in very low birthweight (VLBW) infants, but limited data exist regarding its impact on bronchopulmonary dysplasia (BPD). Objective: To prospectively study the impact of OMM received in the neonatal intensive care unit (NICU) on the risk of BPD and associated costs. Design/methods: A 5-year prospective cohort study of the impact of OMM dose on growth, morbidity and NICU costs in VLBW infants. OMM dose was the proportion of enteral intake that consisted of OMM from birth to 36 weeks postmenstrual age (PMA) or discharge, whichever occurred first. BPD was defined as the receipt of oxygen and/or positive pressure ventilation at 36 weeks PMA. NICU costs included hospital and physician costs. Results: The cohort consisted of 254 VLBW infants with mean birth weight 1027±257 g and gestational age 27.8±2.5 weeks. Multivariable logistic regression demonstrated a 9.5% reduction in the odds of BPD for every 10% increase in OMM dose (OR 0.905 (0.824 to 0.995)). After controlling for demographic and clinical factors, BPD was associated with an increase of US41 929 in NICU costs. Conclusions: Increased dose of OMM feedings from birth to 36 weeks PMA was associated with a reduction in the odds of BPD in VLBW infants. Thus, high-dose OMM feeding may be an inexpensive, effective strategy to help reduce the risk of this costly multifactorial morbidity.